2002
DOI: 10.1152/nips.01400.2002
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Fluid Transport: a Lymphatic Perspective

Abstract: The textbook view that projections of the arachnoid membrane into the cranial venous sinuses represent the primary cerebrospinal fluid (CSF) absorption sites seems incompatible with many clinical and experimental observations. On balance, there is more quantitative evidence suggesting a function for extracranial lymphatic vessels than exists to support a role for arachnoid villi and granulations in CSF transport.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
73
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(74 citation statements)
references
References 15 publications
0
73
0
1
Order By: Relevance
“…The conventional view of CSF transport is that CSF is absorbed from the subarachnoid compartment through the arachnoid villi or granulations that project into the venous sinuses of the dura mater on the convexity of the brain. 3) The hydrostatic pressure difference between the CSF compartment and venous sinuses may be the driving force for absorption. 3) Cerebral venous hypertension resulting from direct arteriovenous shunting and/or obstruction of the sinuses may cause problems with the CSF dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…The conventional view of CSF transport is that CSF is absorbed from the subarachnoid compartment through the arachnoid villi or granulations that project into the venous sinuses of the dura mater on the convexity of the brain. 3) The hydrostatic pressure difference between the CSF compartment and venous sinuses may be the driving force for absorption. 3) Cerebral venous hypertension resulting from direct arteriovenous shunting and/or obstruction of the sinuses may cause problems with the CSF dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Also, spinal arachnoid villi along the nerve roots have been suggested as an absorption route for CSF (28). In animals, lymphatic drainage pathways have been shown to play an important role for CSF clearance (5,27,46). The existence of a lymphatic drainage pathway in humans remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The arachnoid villi in the superior sagittal sinus have generally been thought to be the main site for CSF absorption in humans (2, 40). However, lymphatic drainage pathways have been shown in animal studies to play an important role for CSF clearance (5,27,46). The existence of this pathway in humans remains unclear.…”
mentioning
confidence: 99%
“…This system contributes to clearance of small molecules and proteins from interstitial fluid to lymph nodes in the neck and spine, and Johnston and colleagues have shown that it accounts for a large fraction of CSF clearance. [103][104][105][106] Early studies established rapid distribution of tracers inserted into interstitial fluid or CSF throughout the entire brain via perivascular fluid, and rates of tracer delivery to lymph nodes varied with head position, intracranial pressure, arterial pulsations, and other factors. 107,108 Amyloid-beta, 14 C-metabolites of [ 14 C]glucose, and fluorescent tracers are cleared via this pathway by mechanisms involving astrocytic water movements mediated by aquaporins.…”
Section: Some Speculations: Hypoglycemic Glycogenolysis Mitochondriamentioning
confidence: 99%